The efficiency analysis of the three-link switching field of the digital switching system EWSD - Chaban, Ksenia (Видавництво Львівської політехніки, 2012)
This work has an educational and research character and aims to analyze the efficiency of the three-link SN switching field structure of the modern digital switching system EWSD according to the defined efficiency criterias of the switching systems.
Keywords: Digital switching field; Criteria of the efficiency; Time module; Equivalent switching point